Analisis Optimalisasi Penjualan Produk Cireng Menggunakan Metode Grafik Linier Programming pada UMKM Serang - Enah Alia Sova; Rodifah Rodifah; Ai Khoerumisa; Sumyanah; Bambang Hermawan (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2026)
MSMEs Traditional culinary MSMEs play a vital role in the Indonesian economy through job creation, income equality, and preservation of local culture. However, limited capital, raw materials, and labor, as well as unsystematic production planning, mean that MSME production decisions are still intuitive, leading to inefficiencies and suboptimal profits. A case study of MSME Sostang Tijang Bruno, a Sundanese cireng producer, shows that cireng production is still based on experience without clear calculations, resulting in a mismatch between production and demand and waste of raw materials. This study aims to optimize cireng production volume using the Graphical Linier Programming method to maximize profits by considering constraints on raw materials, working time, and market capacity. Data were obtained through observation, interviews, and documentation. The decision variables were the production volume of original chicken-filled cireng and spicy chicken-filled cireng. The analysis results showed an optimal production combination of 2.93 kg of original chicken-filled cireng and 0.53 kg of spicy chicken-filled cireng with a maximum profit of Rp499,000 per day. This method is expected to help MSMEs make more efficient and rational production decisions